Sensitivity optimization of a Double-Gated ISFET pH-sensor with HfO2/SiO2 gate dielectric stack. (December 2021) - Khwairakpam, Dayananda Singh; Pukhrambam, Puspa Devi
Abstract: This paper investigates the sensitivity enhancement of Ion-Sensitive Field Effect Transistor (ISFET) pH-sensor using double-gate operation and illustrates how different structure modifications between the top and back oxides give different sensitivity gain factors. The gain factor is controlled through top and back oxide thickness, channel thickness and SiGe channel material. The sensitivity at the back gate is 59.52 mV/pH (27 °C) and the amplified sensitivity at the front gate reaches 476.54 ±33 mV/pH (27 °C). Furthermore, the issues related to high sensitivity-amplification such as sensitivity variation and dielectric breakdown are discussed, followed by optimization of the device structure in the linear regime to overcome them. Stacking a thin HfO 2 layer over the top SiO2 layer helps in preventing dielectric breakdown at high sensitivity analysis. Synopsys TCAD is utilized for this proposed work with the electrolyte material and site-binding reactions being modeled through user-defined features of TCAD with explicit references from experimental data. Graphical abstract: Highlights: Ion-Sensitive Field Effect Transistor (ISFET). Threshold voltage variation in Double-Gate MOSFET. Sensitivity optimization techniques. Dielectric Breakdown.